Fifty years of hemodialysis in Ghana-current status, utilization and cost of dialysis services - Elliot Koranteng Tannor; Kojo Hutton-Mensah; Priscilla Opare-Addo; Martin Kofi Agyei; Kwadwo Faka Gyan; Abdul-Jalil Inusah; Beatrice Irene Nyann; Kwabena Amo-Antwi; Valerie Luyckx; Ikechi Okpechi (BMC, 2023)
Abstract Background Kidney failure is common in Ghana. Haemodialysis (HD) is the most common treatment modality for survival. Although, HD has been available in Ghana for 50 years, the majority of patients who develop kidney failure cannot access it. We describe the state of HD, dialysis prevalence, its utilization and cost of HD after fifty years of dialysis initiation in Ghana. Methods A situational assessment of HDs centres in Ghana was conducted by surveying nephrologists, doctors, nurses and other health care professionals in HD centres from August to October 2022. We assessed the density of HD centres, number of HD machines, prevalence of nephrologists, number of patients receiving HD treatment and the cost of dialysis in private and government facilities in Ghana. Results There are 51 HD centres located in 9 of the 16 regions of Ghana. Of these, only 40 centres are functioning, as 11 had shut down or are yet to operate. Of the functioning centres most (n = 26, 65%) are in the Greater Accra region serving 17.7% of the population and 7(17.5%) in the Ashanti region serving 17.5% of the population in Ghana. The rest of the seven regions have one centre each. The private sector has twice as many HD centers (n = 27, 67.5%) as the public sector (n = 13,32.5%). There are 299 HD machines yielding 9.7 HD machines per million population (pmp) with a median of 6 (IQR 4-10) machines per centre. Ghana has 0.44 nephrologists pmp. Currently, 1195 patients receive HD, giving a prevalence of 38.8 patients pmp with 609(50.9%) in the private sector. The mean cost of HD session is US $53.9 ± 8.8 in Ghana. Conclusion There are gross inequities in the regional distribution of HD centres in Ghana, with a low HD prevalence and nephrology workforce despite a high burden of CKD. The cost of haemodialysis remains prohibitive and mainly paid out-of-pocket limiting its utilization.